More standing and just as productive: Effects of a sit-stand desk intervention on call center workers’ sitting, standing, and productivity at work in the Opt to Stand pilot study - Chau, Josephine Y. (Prev Med Rep, 2015)
This study evaluated the effects of sit-stand desks on workers' objectively and subjectively assessed sitting, physical activity, and productivity. This quasi-experimental study involved one intervention group (n = 16) and one comparison group (n = 15). Participants were call center employees from two job-matched teams at a large telecommunications company in Sydney, Australia (45% female, 33 ± 11 years old). Intervention participants received a sit-stand desk, brief training, and daily e-mail reminders to stand up more frequently for the first 2 weeks post-installation. Control participants carried out their usual work duties at seated desks. Primary outcomes were workday sitting and physical activity assessed using ActivPAL or ActiGraph devices and self-report questionnaires. Productivity outcomes were company-specific objective metrics (e.g., hold time, talking time, absenteeism) and subjective measures. Measurements were taken at baseline, 1, 4, and 19 weeks post-installation. Intervention participants increased standing time after 1 week (+ 73 min/workday (95% CI: 22, 123)) and 4 weeks (+ 96 min/workday (95% CI: 41, 150)) post-intervention, while control group showed no changes. Between-group differences in standing time at one and 4 weeks were + 78 (95% CI: 9, 147) and + 95 min/workday (95% CI: 15, 174), respectively. Sitting time in the intervention group changed by − 64 (95% CI: − 125, − 2), − 76 (95% CI: − 142, − 11), and − 100 min/workday (95% CI: − 172, − 29) at 1, 4, and 19 weeks post-installation, respectively, while the control group showed no changes. No changes were observed in productivity outcomes from baseline to follow-up in either group. Sit-stand desks can increase standing time at work in call center workers without reducing productivity.